The Role of Information Technology in Improving the Quality and Efficiency of the Process of Building and Construction in Uzbekistan - Narzievich, Tukhtashov Baxadir (European Journal of Life Safety and Stability (2660-9630), 2021)
This article focuses on the coverage of technological processes in improving the quality of buildings and structures under construction in Uzbekistan. In addition, the cost of construction and installation work is taken into account.